Genome-wide comparison reveals large structural variants in cassava landraces - Landi, M.; Carluccio, A.V.; Shah, T.; Niazi, A.; Stavolone, L.; Falquet, L.; Gisel, A.; Bongcam-Rudloff, E. (2025)
Background Structural variants (SVs) are critical for plant genomic diversity and phenotypic variation. This study investigates a large, 9.7 Mbp highly repetitive segment on chromosome 12 of TMEB117, a region not previously characterized in cassava (Manihot esculenta Crantz). We aim to explore its presence and variability across multiple cassava landraces, providing insights into its genomic significance and potential implications.